2012
DOI: 10.1038/bjc.2012.517
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cancer in the general population: a blinded case–control study of p53 autoantibodies in colorectal cancer

Abstract: Background:Recent reports from cancer screening trials in high-risk populations suggest that autoantibodies can be detected before clinical diagnosis. However, there is minimal data on the role of autoantibody signatures in cancer screening in the general population.Methods:Informative p53 peptides were identified in sera from patients with colorectal cancer using an autoantibody microarray with 15-mer overlapping peptides covering the complete p53 sequence. The selected peptides were evaluated in a blinded ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 35 publications
3
97
2
1
Order By: Relevance
“…The authors found that the presence of autoantibodies to both proteins was associated to a better outcome of the disease. Finally, in another recent study, an association of high levels of autoantibodies to the aberrant glycopeptide MUC4TR5 with a risk of death in CRC patients has been observed (Pedersen et al 2013).…”
Section: Identification Of the Minimum Number Of Taas To Be Included mentioning
confidence: 97%
See 1 more Smart Citation
“…The authors found that the presence of autoantibodies to both proteins was associated to a better outcome of the disease. Finally, in another recent study, an association of high levels of autoantibodies to the aberrant glycopeptide MUC4TR5 with a risk of death in CRC patients has been observed (Pedersen et al 2013).…”
Section: Identification Of the Minimum Number Of Taas To Be Included mentioning
confidence: 97%
“…A predictor panel composed of a panel of 7 CRC-specific TAAs achieved an AUC of 90 % and a sensitivity of 88.2 % and specificity of 82.6 % for early stages (Duke's stage A and B) (Barderas et al 2012). It has also been reported that humoral responses to p53 can appear in normal-risk individuals between 1.0 and 3.8 years before clinical diagnosis of CRC (Pedersen et al 2013).…”
Section: Early Responsesmentioning
confidence: 97%
“…This approach has been used to develop assays which can detect different types of cancer, such as breast cancer [13][14][15], lung cancer [16][17][18] and colorectal cancer [19]. In these assays, autoantibodies to p53, c-myc, HER-2, NY-ESO-1, BRCA1, BRCA2, MUC1, cyclin B1, CEA, CAGE, GBU4-5, annexin 1, SOX2, HuD, MAGE A4 and FOXP3, were studied and specific autoantibodies have been reported to be present in sera of patients before clinical diagnosis of cancer.…”
Section: Figurementioning
confidence: 99%
“…These antigens are frequently expressed in cancer cells and can generate variants proteins that lack immunological tolerance, leading to the induction of autoantibodies. By employing glycopeptide array displaying a comprehensive library of glycopeptides and glycoproteins derived from human mucins MUC1 and MUC4 could be used as biomarkers for early detection of many types of cancer with high specificity [76,77].…”
Section: Autoantibodies Based Arrays As Biomarker In Early Detection mentioning
confidence: 99%